Quinolizinium-based tunable pH fluorescent probes for imaging in live cells. (September 2022) - Sit, Hoi-Yi; Deng, Jie-Ren; Chan, Wing-Cheung; Ko, Ben Chi-Bun; Wong, Man-Kin
Abstract: A new class of quinolizinium-based tunable pH fluorescent probes for cell imaging was developed. The probes showed turn "On" fluorescence response upon acidification brought by a modulation of photoinduced electron transfer (PET) from the N, N-dialkyl aniline substituent to the quinolizinium core skeleton. These novel PET-based pH fluorescent probes displayed tunable emission properties in between 478 and 509 nm. Also, the probes exhibited tunable pH responsiveness with pKa ranging from <2.1 to 6.1 contributed by the steric effect of N, N-dialkyl anilines. They were successfully applied to in vivo pH sensing in lysosome in live cells. Graphical abstract: Image 1 Highlights: A new class of PET-based pH fluorescent probes was developed based on a quinolizinium core skeleton with an aniline moiety. These novel PET-based pH fluorescent probes exhibited tunable emission properties and pH responsiveness. The steric effect of N, N-dialkyl anilines resulted in different pKa values of the pH fluorescent probes. They were successfully applied to pH sensing in vivo in lysosome of live cells.